1972
DOI: 10.1021/j100650a021
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of aqueous solutions of fluorinated surfactants

Abstract: The surface tension and the solubility of aqueous solutions of fluorinated surfactants (CJBVhSOsM, C7F15-COOM, etc.) have been measured. The cmc's and the Krafft points of the fluorinated surfactants were determined from these data. The cmc of fluorinated surfactant is close to that of ordinary surfactant whose hydrocarbon chain length is about 1.5 times longer than a fluorocarbon chain. This relation is explained assuming the free energy change of transferring the -CF2group from the singly dispersed state (aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
256
3
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(289 citation statements)
references
References 0 publications
29
256
3
1
Order By: Relevance
“…It has been reported that the cmcs of fluorinated surfactants are close to those of hydrogenated surfactants whose hydrocarbon chain length is ca. 1.5 times longer than the fluorocarbon chain 25 . On the basis of this empirical rule, in the case of CC-9,9-EsH2F4, for example, the effective hydrocarbon chain length from the ester unit is estimated as 4 1.5 2 8.…”
Section: Dilute Aqueous Solution Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been reported that the cmcs of fluorinated surfactants are close to those of hydrogenated surfactants whose hydrocarbon chain length is ca. 1.5 times longer than the fluorocarbon chain 25 . On the basis of this empirical rule, in the case of CC-9,9-EsH2F4, for example, the effective hydrocarbon chain length from the ester unit is estimated as 4 1.5 2 8.…”
Section: Dilute Aqueous Solution Propertiesmentioning
confidence: 89%
“…This is the first report focusing on the physicochemical properties of oleic acid-based gemini surfactants in aqueous solution as a function of the hydrophobic chain type. We have assessed the dilute aqueous solution properties at pH 9 in the presence of 10 mmol dm 3 NaCl at 25 by means of static surface tension, pyrene fluorescence, and dynamic light scattering DLS measurements. We have also studied the temperature-concentration phase diagrams of the surfactants disodium salts at concentrations up to 80 wt .…”
mentioning
confidence: 99%
“…We do note, however, that previous work has established both the effects of chain branching and the head group counterion (e.g., H + , Na + , Li + , K + , NH 4 + , Mg 2+ ) on the physicochemical properties of PFAs. [130] Although only one branched PFA was available for testing in this historical study (the terminal monomethyl branched C 8 PFCA 88), both branching and the counterion identity had significant effects on properties such as the critical micelle concentrations and Krafft points. Consequently, future work will need to better define the counterion effects on PFA behavior, but with our current level of uncertainty on this front, a default to assessments with the acid form seems the most productive first step.…”
mentioning
confidence: 99%
“…The aggregates may be small premicelles such as dimers or trimers. It is known that the CMC for fluorocarbon-type surfactants follows an equivalence of 1 CF 2 to 1.5 CH 2 units of hydrocarbon-type surfactants 18 . Therefore, it is expected that the CMC of fluorocarbon-type C 6 F C 3 AdAB be equal to that of hydrocarbontype C 12 AdAB; in other words that its alkyl carbon number is1.5 times the carbon number in the fluorocarbon chain, in addition to the 3 carbons from the propyl chain.…”
Section: Adsorption Properties At Air/water Interfacementioning
confidence: 99%